An alternate method for extracting DNA from environmentally challenged teeth for improved DNA analysis. (January 2016) - Hughes-Stamm, Sheree; Warnke, Frauke; van Daal, Angela
Highlights: A minimal-invasive filing method for retrieving dentine from teeth is reported. The filing method yielded more DNA per g of dentine than by grinding the entire root. The filing method produced more complete and balanced STR profiles than the grinding method. The filing method was more labour intensive but in general yielded better STR profiles. Abstract: A grinding-free method to extract DNA from teeth via a direct minimal-invasive retrograde approach to the pulp cavity and dentine was compared to a standard grinding/pulverisation method. This alternate method uses endodontic dental files to access the root canals and pulp cavity for tissue and dentine harvest via the apical end of the roots and avoids mechanical damage to the crown and root morphology. In contrast, other methods require pulverisation of the whole root or tooth, transection or destruction of the occlusal surface to gain access to the DNA in the root canals and pulp chamber. This study compared two methods for preparing dentine powder from the roots of environmentally challenged teeth for forensic DNA analysis. We found that although the filing method was more laborious, and produced less dentine powder, the amount of amplifiable DNA per milligram of powder was substantially higher with the filing method compared to grinding the entire root. In addition, the number of short tandem repeat (STR) alleles detected and the peak height ratios of the STR profiles were notably higher. Although several other methods of extracting DNA-rich tissue from the pulp chamber of teeth have previously been reported, the method presented in this study is minimally invasive, thereby allowing the preservation of tooth and crown morphology.